Basic fibroblast growth factor supports the survival of cerebral cortical neurons in primary culture. - Morrison, R S (1986)
Bovine basic fibroblast growth factor (bFGF) is a potent mitogen isolated from bovine pituitary glands and brain. The addition of homogeneous bFGF to primary cultures of rat cerebral cortical neurons markedly enhances cell survival and elaboration of neurites. These effects are dose-dependent, with optimal stimulation occurring at a concentration of 500 pg/ml. Maintenance of survival and neurite outgrowth require the continuous presence of bFGF. Other growth factors, such as thrombin, platelet-derived growth factor, beta nerve growth factor, and interleukin 2, have no effect on neuronal survival or process formation. Although the cellular site(s) of bFGF synthesis has not yet been established, these results suggest that bFGF may function as a neurotrophic agent in the central nervous system.